2018
DOI: 10.1186/s12967-018-1617-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved CD4 T cell profile in HIV-infected subjects on maraviroc-containing therapy is associated with better responsiveness to HBV vaccination

Abstract: BackgroundMaraviroc-containing combined antiretroviral therapy (MVC-cART) improved the response to the hepatitis B virus (HBV) vaccine in HIV-infected subjects younger than 50 years old. We aimed here to explore the effect of this antiretroviral therapy on different immunological parameters that could account for this effect.MethodsWe analysed baseline samples of vaccinated subjects under 50 years old (n = 41). We characterized the maturational subsets and the expression of activation, senescence and prone-to-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Hundreds of millions of infected individuals have chronic hepatitis B (CHB), which represents a serious threat to public health (1,2). China is a moderately endemic area of HBV infection, the treatment of which is thus one of the serious challenges for China's medical community (3,4). After initial acute infection, certain individuals continue to be infected, the disease gradually turns into CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of millions of infected individuals have chronic hepatitis B (CHB), which represents a serious threat to public health (1,2). China is a moderately endemic area of HBV infection, the treatment of which is thus one of the serious challenges for China's medical community (3,4). After initial acute infection, certain individuals continue to be infected, the disease gradually turns into CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found higher frequencies of all the CD4 and CD8 maturational subsets expressing the proliferation marker Ki67 in the non-responders to the influenza vaccine than the responders. In a recent work, we observed an inverse association between the magnitude of the HBV vaccine response and the frequency of proliferating CD4 T-cells in a cohort of HIV-infected patients [31]. As far as we know, no other previous evidence has associated a poor response to vaccination with conventional T-cell proliferation.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, we previously showed that human immunodeficiency virus (HIV)-infected subjects who did not respond to a hepatitis B virus (HBV) vaccine had a higher baseline frequency of Tregs than those who did respond [24, 31]. The fact that high baseline Treg frequencies impaired the response to vaccination in the elderly and HIV-infected subjects reinforces Treg increases in the steady states of both scenarios as a common feature of immunosenescence [27], which could compromise the ability of the immune system to mount a proper immune response [2126, 31]. Further research about the underlying mechanism of these immunosenescence-related Treg increases is needed to develop novel approaches aimed to improve vaccine responsiveness in these scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature also favors the use of MVC in selected clinical settings given its immune-modulating and anti-inflammatory effects. A recent study showed improved responsiveness to HBV vaccination in MVC-treated subjects, possibly due to reduced CD4+ T-cell activation and proliferation [ 101 ]. Another report demonstrated lower levels of monocyte activation in individuals receiving MVC compared with those on MVC-free regimes [ 102 ], supporting in vitro evidence on the possible role of CCR5 inihitors in hindering atherosclerotic plaque formation [ 103–105 ].…”
Section: Differences In Immune Recovery According To Cart Regimen?mentioning
confidence: 99%